A method for the automated long‐term monitoring of three‐spined stickleback Gasterosteus aculeatus shoal dynamics. Issue 4 (4th March 2014) - Kleinhappel, T. K.; Al‐Zoubi, A.; Al‐Diri, B.; Burman, O.; Dickinson, P.; John, L.; Wilkinson, A.; Pike, T. W.
<x xml:space="preserve">Abstract</x> This paper describes and evaluates a flexible, non‐invasive tagging system for the automated identification and long‐term monitoring of individual three‐spined sticklebacks Gasterosteus aculeatus. The system is based on barcoded tags, which can be reliably and robustly detected and decoded to provide information on an individual's identity and location. Because large numbers of fish can be individually tagged, it can be used to monitor individual‐ and group‐level dynamics within fish shoals.